2023
DOI: 10.30630/joiv.7.3.1751
|View full text |Cite
|
Sign up to set email alerts
|

Max Feature Map CNN with Support Vector Guided Softmax for Face Recognition

Herdianti Darwis,
Zahrizhal Ali,
Yulita Salim
et al.

Abstract: Face recognition has made significant progress because of advances in deep convolutional neural networks (CNNs) in addressing face verification in large amounts of data variation. When image data comes from different sources and devices, the identifiability of other classes and the presence of profile face data can lead to inaccurate and ambiguous classification because other classes lack discriminatory power. Furthermore, using a complex architecture with many deep convolutional layers can become very slow in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…CNN technique, also known as ConvNets, uses a deep learning tool [20]. The usage of CNNs is due to their effectiveness in pattern recognition, especially in recognizing objects, people's faces, and scene images [21]. Moreover, we also combined CNN with Remini image enhancer to boost the accuracy of social distancing detectors, and it has been observed that the accuracy has improved to 90%.…”
Section: Data Analysis and Classificationmentioning
confidence: 99%
“…CNN technique, also known as ConvNets, uses a deep learning tool [20]. The usage of CNNs is due to their effectiveness in pattern recognition, especially in recognizing objects, people's faces, and scene images [21]. Moreover, we also combined CNN with Remini image enhancer to boost the accuracy of social distancing detectors, and it has been observed that the accuracy has improved to 90%.…”
Section: Data Analysis and Classificationmentioning
confidence: 99%